Textual Sentence - Mfreg, Hasan Mohammed (Journal of Humanities & Social Sciences, 2019)
This research focuses on the definition of the term of textual sentence by explaining its definition, indicating the type of semantics within it and clarifying how to identify its boundaries. However, it will begin explaining in details the so-called system sentences, which will help to recognize differences between them and the textual ones through demonstrating the concept of system sentences and the type of semantics inside them. The result of this research is to arrive at a more acceptable sentence definition than the definitions of former Arab and Western linguists. This research, also, will also contribute to solving the apparent problem in Arabic writing which is the confusion that a writer encounters when he wants to end a sentence.